The Relationship between Attitudes toward Death and Emotional Intelligence, Personality, Resilience, and Justice Beliefs: A Cross-Sectional Study of Midwives in Greece - Evangelos Tzamakos; Dimitra Metallinou; Antigoni Sarantaki; Maria Tigka; Aikaterini Lykeridou; Christina Nanou (MDPI AG, 2024)
Midwifery practice inevitably includes miscarriages, stillbirths, and neonatal deaths. The aim of the present study was to investigate the relationship between attitudes toward death and emotional intelligence, personality, resilience, and justice beliefs among midwives in Greece. A descriptive cross-sectional study was conducted from 2020 to 2022 among 348 midwives employed in public hospitals, in regional health authorities, or as independent professionals. Research instruments included the Death Attitude Profile-Revised, the Connor-Davidson Resilience Scale, the Trait Emotional Intelligence Questionnaire-Short Form, the Eysenck Personality Questionnaire, and the Belief in a Just World scale. The results revealed that greater emotional intelligence was significantly associated with higher scores in the escape acceptance subscale. Midwives scored low on the neutral acceptance subscale (2.9 ± 0.8), with the highest score being recorded in the escape acceptance subscale (4.6 ± 1.0), which was significantly associated with greater emotional intelligence. Neuroticism was significantly associated with the death avoidance, approach acceptance, fear of death, and escape acceptance subscales. Finally, the subscale of distributive justice beliefs for self and others was significantly associated with the subscales of death avoidance and approach acceptance. These findings highlight the nuanced perspectives within the healthcare community. As we delve deeper into the complexities of end-of-life care, understanding these diverse attitudes is crucial for providing comprehensive and empathetic support to both patients and healthcare professionals.